Logical Spaces and Subjunctive Tenses - Rui Marques (Languages, 2024)
Apparently, Subjunctive tenses express temporal location, and, in some constructions, the past subjunctive can also express modal values. A long-standing debate exists over whether—even in the latter case—verbal tenses are temporal operators or whether in some constructions they convey temporal meaning, and in others they have a modal value, maybe derived from their basic temporal meaning. The assumption that the basic meaning of subjunctive tenses are of a temporal nature is challenged by the fact that the future subjunctive, which exists in Portuguese, has the same temporal interpretation as the present subjunctive, with which it is in complementary distribution. Moreover, no clear modal difference is observed between the future and present subjunctive tenses. In this paper, I present arguments against the separation of the temporal and modal values of the subjunctive tenses. I posit, instead, that a semantic analysis of subjunctive morphemes must consider ordered pairs of times and possible worlds; only in this way can we adequately capture the observed data and allow a comprehensive view of the system of subjunctive tenses in Portuguese (which will be extendable to Romance languages in general). If we accept this proposal, then the modal as temporal information associated with subjunctive tenses follows naturally, including the systematic futurate reading of subjunctive temporal clauses.